In-Network Adaptation of Video Streams Using Network Processors. (1st June 2009) - Shorfuzzaman, Mohammad; Eskicioglu, Rasit; Graham, Peter
Abstract : The increasing variety of networks and end systems, especially wireless devices, pose new challenges in communication support for, particularly, multicast-based collaborative applications. In traditional multicasting, the sender transmits video at the same rate and resolution to all receivers independent of their network characteristics, end system equipment, and users' preferences about video quality and significance. Such an approach results in resources being wasted and may also result in some receivers having their quality expectations unsatisfied. This problem can be addressed, near the network edge, by applying dynamic, in-network adaptation (e.g., transcoding) of video streams to meet available connection bandwidth, machine characteristics, and client preferences. In this paper, we extrapolate from earlier work of Shorfuzzaman et al. 2006 in which we implemented and assessed an MPEG-1 transcoding system on the Intel IXP1200 network processor to consider the feasibility of in-network transcoding for other video formats and network processor architectures. The use of "on-the-fly" video adaptation near the edge of the network offers the promise of simpler support for a wide range of end devices with different display, and so forth, characteristics that can be used in different types of environments.